1998
DOI: 10.1177/106689699800600306
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomatoid Papulosis Associated with Cutaneous T-Cell Signet Ring Lymphoma

Abstract: The authors describe a new case of cutaneous T-cell lymphoma of signet ring cell type with CD-30 (Ki-t) expression. The patient was a 52-year-old woman with a 20-year history of recurrent papulonodular lesions characteristic of lymphomatoid papulosis (LP). Subsequent to developing the signet ring cell lymphoma (SRL) the patient's cutaneous lesions did not resolve as previously, and a skin biopsy showed a diffuse proliferation of atypical lymphoid cells with cytoplasmic vacuoles. SRL was first reported in 1985 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“… 4 However, there are reported cases of post-transplant CD30+ anaplastic large cell lymphoma (ALCL) associated with EBV. 5 Regardless, as in the case of our patient, the pathogenesis of CD30+ T-cell lymphoma can occur independent of EBV. CD30+ cutaneous lymphoproliferative disorders encompass the second most common form of cutaneous lymphomas according to the World Health Organization and European Organization for Research and Treatment of Cancer Classification (WHO-EORTC).…”
Section: Discussionsupporting
confidence: 48%
“… 4 However, there are reported cases of post-transplant CD30+ anaplastic large cell lymphoma (ALCL) associated with EBV. 5 Regardless, as in the case of our patient, the pathogenesis of CD30+ T-cell lymphoma can occur independent of EBV. CD30+ cutaneous lymphoproliferative disorders encompass the second most common form of cutaneous lymphomas according to the World Health Organization and European Organization for Research and Treatment of Cancer Classification (WHO-EORTC).…”
Section: Discussionsupporting
confidence: 48%
“…6 For instance, the neutrophil-rich (pyogenic) variant has emerged as a subtype of primary cutaneous ALCL, which may have different clinical parameters than the conventional type. 6,[8][9][10][11][12] We believe this case to represent perhaps the first case of a primary cutaneous CD30+ T-cell PTLD with signet ring cells. 6,[8][9][10][11][12] We believe this case to represent perhaps the first case of a primary cutaneous CD30+ T-cell PTLD with signet ring cells.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Grogan et al 10 demonstrated the cells had a vacuolar staining in "pools" for several T-cell antigens and, along with the ultrastructural evidence, concluded that aberrant membrane recycling may be implicated in the formation of the vacuoles. Negative staining with mucicarmine, 11 alcian blue, and oil red-O 9 argues against the material being mucin or fat.…”
Section: Discussionmentioning
confidence: 99%